The Impact of Continuous Passive Motion on Heterotopic Ossification Maturation. (December 2021) - Vasileiadis, George I.; Varvarousis, Dimitrios N.; Manolis, Ioannis; Ploumis, Avraam
Abstract : Abstract: Heterotopic ossification is the formation of pathological bone in soft tissues. It is postulated that continuous passive motion is a helpful adjuvant in the halt of the heterotopic ossification progression and the maintenance or increase of the joint mobility. The purpose of this clinical case study is to present the effectiveness of continuous passive motion. A 46-yr-old male patient experiencing right hemiparesis arrived in our rehabilitation department with limitation on passive flexion of the right hip. On x-ray of the pelvis, immature heterotopic bone formation was found. To halt this ongoing process of heterotopic bone formation, a program of continuous passive motion was implemented. In addition, risedronate was administrated. We started the continuous passive motion at 50 degrees of flexion for 30 mins that was increased to 100 degrees for 3 hrs daily. The final range of motion at the hip was: flexion 85 degrees, extension 0 degrees, internal rotation 10 degrees, external rotation 10 degrees, abduction 10 degrees, and adduction 10 degrees. Based on our results, continuous passive motion plays a role in heterotopic ossification maturation. The effectiveness of continuous passive motion implementation against HO should be further investigated for selected cases. Abstract : Supplemental digital content is available in the text.